PREDICTING CPA EXAMINATION RESULTS. - Kane, Robert L.; Traxler, Arthur E. (The Accounting Review, 1954)
The article focuses on the extent to which predictions can be made about certified public accountants (CPA) examination results. Studies of the use of the Institute sponsored Orientation and Achievement Tests as a means of making such predictions have produced encouraging results. On the basis of these studies, which are of limited scope, it appears that reasonably accurate predictions can be made in many instances. There are many benefits which will accrue to the profession and to individuals if fairly accurate predictions can be made that a particular individual should be able to pass the CPA examination; that another individual is unlikely to pass, and that still another one has a slight chance to pass. Such predictions would aid appreciably in guidance work, and would be of value to employers. Predictive devices might be used by state examining boards in various ways. Boards might be aided in their efforts to encourage potentially able men to continue preparation and to discourage those who are obviously not ready to take the examination as well as those who may never qualify. Predictive devices might aid considerably in reducing failures.